2006
DOI: 10.1111/j.1365-2052.2005.01409.x
|View full text |Cite
|
Sign up to set email alerts
|

Albinism in the domestic cat (Felis catus) is associated with a tyrosinase (TYR) mutation

Abstract: SummaryAlbino phenotypes are documented in a variety of species including the domestic cat. As albino phenotypes in other species are associated with tyrosinase (TYR) mutations, TYR was proposed as a candidate gene for albinism in cats. An Oriental and Colourpoint Shorthair cat pedigree segregating for albinism was analysed for association with TYR by linkage and sequence analyses. Microsatellite FCA931, which is closely linked to TYR and TYR sequence variants were tested for segregation with the albinism phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 12 publications
1
64
0
8
Order By: Relevance
“…Tyr mutants have been identified in many animals including the mouse [2,23], rabbit [1], rat [3], cat [11], and ferret [4]. Mutations in Slc45a2 have been identified in an increasing number of animal species [9,10,26,27,33,37], and the phenotype of Slc45a2 varies from hypopigmentation as severe as that seen in OCA1 to some pigmentation with brown hair and eyes [13].…”
Section: Discussionmentioning
confidence: 99%
“…Tyr mutants have been identified in many animals including the mouse [2,23], rabbit [1], rat [3], cat [11], and ferret [4]. Mutations in Slc45a2 have been identified in an increasing number of animal species [9,10,26,27,33,37], and the phenotype of Slc45a2 varies from hypopigmentation as severe as that seen in OCA1 to some pigmentation with brown hair and eyes [13].…”
Section: Discussionmentioning
confidence: 99%
“…Les chats uniformément blancs peuvent présenter des yeux bleus, des yeux or, verts ou impairs. Remarquons en effet que l'absence de pigmentation de l'oeil, chez le chat, ne se traduit pas par une couleur rouge des yeux, comme chez de nombreux mammifères albinos, mais par une couleur bleue très pâle (Imes et al 2006). La couleur blanche dominante est gouvernée par le locus W (White) qui possède deux allèles : W (white) dominant qui détermine le blanc et w récessif : l'allèle sauvage qui permet la pigmentation.…”
Section: Absence De Pigmentationunclassified
“…Non-synonymous SNPs occurring in coding regions result in single amino acid polymorphisms, which may affect protein function and lead to pathogenic phenotypes (Capriotti et al, 2011). Previous studies have shown that TYR mutations are associated with albinism in many vertebrates, including humans (Oetting, 2000), rats (Blaszczyk et al, 2005), cattle (Schmutz et al, 2004), cats (Imes et al, 2006), chickens (Liu et al, 2010), and geese (Wang et al, 2014). Peking ducks have a mutation in exon 1 of TYR, but whether this affects the color traits of duck feathers has not been determined.…”
Section: Introductionmentioning
confidence: 99%